PENGARUH PROFITABILITAS, SOLVABILITAS, LIKUIDITAS DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Michelle, Michelle; Zubaidi, Umar Issa (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
Abstract: The aim of this research on firm value is to obtain empirical evidence regarding the effect of profitability, solvability, liquidity, firm size, dividend policy, sales growth, firm age, managerial ownership, and institutional ownership could influence a firm value. This study employs a population of non-financial sector companies listed on the Indonesia Stock Exchange over a 3-year time period, specifically from 2020-2022. The total sample size utilized for this research comprises 65 company and 195 data. The research applies purposive sampling method within a multiple regression model as a data analysis process. The research findings showed that profitability and solvability have positive influence on firm value. Whereas, liquidity, firm size, dividend policy, sales growth, firm age, managerial ownership, and institutional ownership do not significantly impact a firm value.